Integration of Character Values in Integrated Islamic Elementary Schools - Damayanti, Anggi Devira (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This research aims to examine the process of integrating character values at the Muhammadiyah Sukamara Integrated Islamic Elementary School (SDIT). The research method applied is descriptive qualitative with a case study approach. Data collection was carried out through observation, interviews, and documentation. The data analysis technique is carried out through several stages, namely data reduction, data presentation, and drawing conclusions. Research findings indicate that SDIT Muhammadiyah Sukamara has integrated character values such as honesty, responsibility, discipline, cooperation, and empathy into daily activities through various programs and activities. Teachers play an important role in integrating character values, using a holistic approach that involves all elements of the school.